A Self‐Reporting Tetrazole‐Based Linker for the Biofunctionalization of Gold Nanorods. Issue 41 (21st August 2015) - Stolzer, Lukas; Vigovskaya, Antonina; Barner‐Kowollik, Christopher; Fruk, Ljiljana
Abstract A photochemical approach based on nitrile imine‐mediated tetrazole‐ene cycloaddition is introduced to functionalize gold nanorods with biomolecules. For this purpose, a bifunctional, photoreactive linker containing thioctic acid as the Au anchoring group and a tetrazole moiety for the light‐induced reaction with maleimide‐capped DNA was prepared. The tetrazole‐based reaction on the nanoparticles' surface results in a fluorescent pyrazoline product allowing for the spectroscopic monitoring of the reaction. This first example of nitrile imine‐mediated tetrazole‐ene cycloaddition (NITEC)‐mediated biofunctionalization of Au nanorods paves the way for the attachment of sensitive biomolecules, such as antibodies and other proteins, under mild conditions and expands the toolbox for the tailoring of nanomaterials.